Practices of Providing Mpasi Against Stunting Incidents - Idaningsih, Ayu; Astari, Ruri Yuni; Heni, Heni; Nuraeni, Rina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
COMPLETE FOOD PRACTICES IN PREVENTING STUNTINGThis study aims to determine the practice of providing complementary foods in preventing stunting. This research method uses a scoping review to explore more widely the practice of providing complementary foods in preventing stunting in Indonesia. Of the 10 articles considered eligible for review by researchers, the results of the study showed that most subjects in the stunting and non-stunting groups received their first complementary foods at the age of less than six months. Children who received low variations of complementary foods were more often found in the stunting group, while the frequency of low consumption of complementary foods occurred in both groups of subjects aged 9-24 months. The average intake of energy, protein, iron, and zinc differed significantly between the stunting and non-stunting groups aged 6-24 months. In conclusion, it is necessary to increase the variety of complementary foods, consumption of animal food sources, and frequency of consumption in early childhood so that the needs for energy, protein, iron, and zinc intake can be met. Keywords: Complementary foods, Linear Growth, Stunting